Influence of Nasogastric Tubes on Swallowing in Stroke Patients: Measuring Hyoid Bone Movement With Ultrasonography - Ho-Jun Kwak (Annals of Rehabilitation Medicine, 2018)
Objective To investigate the influence of a nasogastric tube (NGT) on swallowing simulated saliva in stroke patients. Methods Three groups of participants were enrolled into the study: group A (20 stroke patients with a NGT), a control group B (25 stroke patients without a NGT), and group C (25 healthy adults with no brain lesions or dysphagia). Participants swallowed 1 mL of water to simulate saliva. Patients in group A were tested twice: once with a NGT (group A1) and once after the NGT was removed (group A2). The distance of hyoid bone movement was measured by subtracting the shortest distance between the mandible and hyoid bone (S) from the distance at resting state (R) measured with ultrasonography. The degree of the movement was calculated by (R–S)/R. The trajectory area of hyoid bone movement (Area) and the interval between the beginning of hyoid bone movement and the moment of the shortest hyoid−mandible approximation (Interval) was calculated by a computer program. Results From group A: R–S and (R–S)/R of group A2 at 1.14±0.36 cm and 0.30±0.09 cm and were significantly greater than those of group A1 at 0.81±0.36 cm and 0.22±0.08 cm (p=0.009 and p=0.005). After removing the NGT as seen in group A2, R–S and (R–S)/R were improved to the level of those of group B at 1.20±0.32 cm and 0.30±0.09 cm (p=0.909 and p=0.997). The Area of group A2 was larger and the Interval of group A2 was shorter than those of group A1 though a comparison of these factors between A2 and A1 did not show a statistically significant difference. Conclusion A NGT interferes with the movement of the hyoid bone when swallowing 1 mL of water in stroke patients though the movement is restored to normal after removing the NGT.